circ-Iqsec1 induces bone marrow-derived mesenchymal stem cell (BMSC) osteogenic differentiation through the miR-187-3p/Satb2 signaling pathway - Lixia Fan; Kaiyun Yang; Ruixuan Yu; Houde Hui; Wenliang Wu (Arthritis Research & Therapy, 2022)
Abstract Background Bone marrow-derived mesenchymal stem cells (BMSCs) are general progenitor cells of osteoblasts and adipocytes and they are characterized as a fundamental mediator for bone formation. The current research studied the molecular mechanisms underlying circRNA-regulated BMSC osteogenic differentiation. Methods Next-generation sequencing (NGS) was employed to study abnormal circRNA and mRNA expression in BMSCs before and after osteogenic differentiation induction. Bioinformatics analysis and luciferase reporting analysis were employed to confirm correlations among miRNA, circRNA, and mRNA. RT-qPCR, ALP staining, and alizarin red staining illustrated the osteogenic differentiation ability of BMSCs. Results Data showed that circ-Iqsec1 expression increased during BMSC osteogenic differentiation. circ-Iqsec1 downregulation reduced BMSC osteogenic differentiation ability. The present investigation discovered that Satb2 played a role during BMSC osteogenic differentiation. Satb2 downregulation decreased BMSC osteogenic differentiation ability. Bioinformatics and luciferase data showed that miR-187-3p linked circ-Iqsec1 and Satb2. miR-187-3p downregulation or Satb2 overexpression restored the osteogenic differentiation capability of BMSCs post silencing circ-Iqsec1 in in vivo and in vitro experiments. Satb2 upregulation restored osteogenic differentiation capability of BMSCs post miR-187-3p overexpression. Conclusion Taken together, our study found that circ-Iqsec1 induced BMSC osteogenic differentiation through the miR-187-3p/Satb2 signaling pathway.